Higher miscarriage rate in subfertile women with endometriosis receiving unbiopsied frozen-warmed single blastocyst transfers - Sachs, M. K.; Makieva, S.; Dedes, I.; Kalaitzopoulos, D. R.; El-Hadad, S.; Xie, M.; Velasco, A.; Stiller, R.; Leeners, B. (Frontiers in Cell and Developmental Biology, 2023)
Background: Assisted reproductive technology treatment is recommended to overcome endometriosis-associated infertility but current evidence is controversial. Endometriosis is associated with lower antral follicle count (AFC) and oocyte yield but similar clinical outcomes compared to controls. Unaffected ovarian stimulation response and embryological outcomes but lower clinical pregnancy and live birth rates and higher miscarriage rates have been reported, implying direct impact on endometrial receptivity. With evidence emerging on the benefit of frozen-warmed and blastocyst stage transfer, we investigated ART outcomes in endometriosis using homogeneous case-control groups. Methods: This is a retrospective observational case-control study including n=66 frozen-warmed unbiopsied single blastocyst transfers of patients with endometriosis and n=96 of women exhibiting idiopathic sterility. All frozen-warmed transfers followed artificial endometrial preparation. Results: In control women, the number of oocytes recovered at oocyte pick up was higher compared to women with endometriosis (15.3±7.1 vs 12.7±5.2, p=0.025) but oocyte maturation index (mature oocytes/total oocytes at oocyte pick up) was significantly higher for endometriosis (48.2% vs 34.0%, p=0.005). The same was shown for the subgroup of 44 endometriosis patients after endometrioma surgery when compared with controls (49.1% vs 34.0%, p=0.014). Clinical pregnancy rate was not higher in endometriosis but was close to significance (47.0% vs 32.3%, p=0.059) while live birth rate was comparable (27.3% vs 32.3%, p=0.746). Miscarriage rate was higher in the endometriosis group (19.7% vs 7.3%, p=0.018). A significantly higher AFC was observed in the control group in comparison with the endometriosis group (16.3±7.6 vs 13.4±7.0, p=0.014). Live birth rate did not differ when comparing all endometriosis cases (p=0.746), ASRM Stage I/II and Stage III/IV (p=0.348 and p=0.888) with the control group but the overall pregnancy rate was higher in ASRM Stage I/II (p=0.034) and miscarriage rate was higher in ASRM Stage III/IV (p=0.030) versus control. Conclusions: Blastocyst transfers in women with endometriosis originate from cycles with lower AFC but higher share of mature oocytes than in control women, suggesting that endometriosis might impair ovarian reserve but not stimulation response. A higher miscarriage rate, independent of blastocyst quality may be attributed to an impact of endometriosis on the endometrium beyond the timing of implantation.